Risks of HIV Infection for Medical Staff. Postexposure Prophylaxis (by the Example of the Sverdlovsk Region) - A. S. Podymova; A. A. Golubkova; V. A. Kukarkina; E. I. Sisin (Эпидемиология и вакцинопрофилактика)
Introduction. The Sverdlovsk region is on the second place among all subjects of the Russian Federation on the level of infestation of the population is HIV. The prevalence of HIV-infected residents of the Sverdlovsk region is 1.6%. This corresponds to a generalized stage of infection. Annually in medical institutions of the Sverdlovsk region up to 4 million patients with HIV infection receive various types of medical care. In these conditions increase the risk of infection employees related to their professional activities.Aims of this study was to assess the completeness and timeliness of post-exposure antiretroviral therapy to employees in case of accidents with exposure to blood and to determine their professional the risks of infection.Materials and methods. The study was conducted on the basis of the Sverdlovsk Regional Center for Prevention and Control of AIDS and the Department of epidemiology of the Ural State Medical University. The authors analyzed 1678 strategic messages in an emergency for 2013-2016.Results. In medical organizations of Sverdlovsk region in 2013 was introduced registration of all emergencies, regardless of the HIV status of the patient. The number of registered accidents was 6.7 ± 0.3 cases per 10 thousand employees. The frequency of emergency situations doctors have1.7 times higher than the average staff and nurses. Among nurses there was a trend to increasing frequency of emergencies, with an annual growth rate of 3.0%. Changes in the frequency of emergency situations, the doctors and nurses are not installed. The authors found considerable variation in the number of accidents according to the official registration and results of the employee survey. The frequency of emergency situations is determined by the profile of the Department, business process, profession, work experience of the employee, day of week and time of day. The number of persons who received chemoprophylaxis during emergency situations, reduced annually. Reasons for the decline were later appeal for help, the failure of prevention and the absence of indications to antiretroviral therapy in low risk of infection. The proportion of doctors who are not receiving antiretroviral treatment was higher than the proportion of paramedical staff and nurses.Conclusion. The prevention of occupational infections require legal regulation. Preventive actions should be focused on the set in the process of research risks.